Selective extraction of silver(I) and photometric determination di-(2-naphthyl)-thiocarbazone (dinaftizone) in the organic phase - Abdullaeva Dilnoza; Giyasov Anvar; Muratkulov Olimjon; Rakhmatova Nodira; Mengliev Sherzod; Zokirova Shokhista; Tursunov Dilshod; Turabdjanov Sadritdin (E3S Web of Conferences, 2024)
A method for the selective, simple and accelerated extraction-photometric determination of silver has been developed, based on the selective extraction of silver(I) from a strongly acidic medium in the presence of iodide ions and dimethylformamide and its complexation with dinaphthizone directly in the organic phase.The apparent molar extinction coefficient of the dinaphthizone complex of silver (I) at a maximum light absorption of 505 nm is 4.75·104. The calibration graph is linear in the range of 0.5-50 μg of silver (I) in 10 ml of extract. The determination of silver is not interfered with by large amounts of foreign ions in quantities up to 100,000 times within 2-5%. The extraction-photometric method developed for the determination of silver is recommended for analyzing silver content in diverse materials, including ores, rocks, industrial wastes, and other substances characterized by complex chemical compositions. Notably, this method is particularly advantageous as it eliminates the need for separating accompanying elements, streamlining the analytical process. By employing this extraction-photometric technique, analysts can achieve accurate and reliable results in the determination of silver content even in samples with intricate chemical matrices. This method enhances efficiency and expedites the analysis of materials that may contain a variety of elements besides silver.